If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2y)(2y + 3x) = 0 Reorder the terms: (3x + 2y)(3x + 2y) = 0 Multiply (3x + 2y) * (3x + 2y) (3x * (3x + 2y) + 2y * (3x + 2y)) = 0 ((3x * 3x + 2y * 3x) + 2y * (3x + 2y)) = 0 Reorder the terms: ((6xy + 9x2) + 2y * (3x + 2y)) = 0 ((6xy + 9x2) + 2y * (3x + 2y)) = 0 (6xy + 9x2 + (3x * 2y + 2y * 2y)) = 0 (6xy + 9x2 + (6xy + 4y2)) = 0 Reorder the terms: (6xy + 6xy + 9x2 + 4y2) = 0 Combine like terms: 6xy + 6xy = 12xy (12xy + 9x2 + 4y2) = 0 Solving 12xy + 9x2 + 4y2 = 0 Solving for variable 'x'. Factor a trinomial. (3x + 2y)(3x + 2y) = 0Subproblem 1
Set the factor '(3x + 2y)' equal to zero and attempt to solve: Simplifying 3x + 2y = 0 Solving 3x + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 3x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = 0 + -2y 3x = 0 + -2y Remove the zero: 3x = -2y Divide each side by '3'. x = -0.6666666667y Simplifying x = -0.6666666667ySubproblem 2
Set the factor '(3x + 2y)' equal to zero and attempt to solve: Simplifying 3x + 2y = 0 Solving 3x + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 3x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = 0 + -2y 3x = 0 + -2y Remove the zero: 3x = -2y Divide each side by '3'. x = -0.6666666667y Simplifying x = -0.6666666667ySolution
x = {-0.6666666667y, -0.6666666667y}
| -4g+6=14 | | 6(x)-x=0 | | (z-2x)(z-2x)= | | 0.015x-0.030=0.030 | | 76=b+4 | | 3y(2+4y+5y^2)= | | 4(x-5)-7-5(3-2x)= | | (a+b)(2a-3b)= | | g-92=-74 | | (7y-4t)(2y+5t)= | | 2m+18=5m-12 | | 15(2x-3)-2(x-2)=26 | | 2x^2-52x+338=0 | | -3d=-75 | | cos(x)+cos(7x)-cos(4x)=0 | | (3t+2q)(7t-9q)= | | u+25=-61 | | 5r^2-55r+15=0 | | cos(x)+cox(7x)-cox(4x)=0 | | 89=n+3 | | 15y^3+12y^2+6y= | | 2+0.3y=11 | | 2(7x+5)=3(3x-2) | | 9(m)=25(m)+22 | | 6m+14m=-16 | | 6b^2=-18b | | 21=2p-9 | | 40+3x+20-5x=30 | | G+2g+6=6g-21 | | 20x-27=73 | | 5(z)+8=4(z)+20 | | 1.3x+3=-1 |